Pharmacology and clinical efficacy of dimethyl fumarate (BG-12) for treatment of relapsing–remitting multiple sclerosis - Ruggieri, Serena (Dove Medical Press, 2014)
The last two decades have seen the introduction of several therapies for multiple sclerosis (MS). These therapies are intended to work at different levels of the disease, typically targeting direct symptom management, brief corticosteroid administration for acute exacerbations, and the regular use of disease-modifying drugs. Nevertheless, in clinical practice, disease-modifying drugs or immunosuppressive treatments are frequently associated with suboptimal response in terms of efficacy and several side effects leading to poor patient adherence, so the proportion of relapsing–remitting MS patients not adequately responding to disease-modifying therapy have been reported to range from 7% to 49%. Natalizumab and fingolimod are the newest US Food and Drug Administration-approved agents that have been added to the MS treatment armamentarium, but their use is limited by a less known safety profile and recognized specific risk. Thus, there is an important need for new therapeutic strategies, especially those that may offer greater patient satisfaction and safer risk profile in order to optimize therapeutic outcomes. A number of potential therapies for MS are now in late-stage development. Effective, safe, and well-tolerated therapies may improve compliance and empower patients with a level of independence not presently possible. To meet these characteristics, most of these therapies are oral compounds. Herein, we review the pharmacology and efficacy of dimethyl fumarate (BG-12) to date and its role in the evolving marketplace.